Covalent Functionalization of PMMA Surface with L‐3, 4‐Dihydroxyphenylalanine (L‐DOPA) to Enhance its Biocompatibility and Adhesion to Corneal Tissue. Issue 1 (5th November 2019) - Sharifi, Roholah; Mahmoudzadeh, Soudabe; Islam, Mohammad Mirazul; Koza, Darrell; Dohlman, Claes H.; Chodosh, James; Gonzalez‐Andrades, Miguel
Abstract: The Boston keratoprosthesis (B‐KPro) is globally the most commonly implanted artificial cornea for patients with severe corneal diseases, particularly those with multiple allograft failures. Despite providing a good visual recovery, the poor adhesion between the poly(methyl methacrylate) (PMMA)‐made stem and the donor tissue poses a challenge, impacting the clinical outcome of the B‐KPro. Using single‐molecule covalent bonding, PMMA surface is functionalized with l ‐3, 4‐dihydroxyphenylalanine (l ‐DOPA) and its chemical, optical, mechanical, and biological properties are studied. The functionalization process significantly improves biocompatibility of PMMA, without affecting its optical and mechanical properties. Human corneal fibroblasts (HCF) and human corneal epithelial cells (HCEp) seeded on l ‐DOPA surface both exhibit greater confluency and metabolic rate compared to those of PMMA during 7‐day cell culture. Moreover, HCF cultured on l ‐DOPA demonstrates a higher expression of ALDH3A1, Ki67, Integrin 1, and FAK with no expression of α‐SMA, compared to those of PMMA, which instead show greater expression of α‐SMA. These suggest that l ‐DOPA surface fosters cellular adhesion, proliferation, and migration, without adversely impacting the phenotype of the cells. This study offers an inexpensive and efficient tactic to modify the surface of materials with l ‐DOPA to achieve the optimal biocompatibility and biointegration of medical devices. Abstract : Covalently functionalized poly(methyl methacrylate) (PMMA) surface with l ‐3, 4‐dihydroxyphenylalanine (l ‐DOPA) is stable, and significantly improves the biocompatibility of the PMMA surface. l ‐DOPA‐functionalized PMMA also preserves the phenotypic characteristics of human corneal fibroblast, supporting cellular adhesion, proliferation, and migration, which may lead to better biointegration of the Boston keratoprosthesis, the most commonly implanted artificial cornea for patients with severe corneal diseases.